2011
DOI: 10.1371/journal.pone.0017900
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of the Vernalization Response in Barley (Hordeum vulgare) Seedlings

Abstract: Temperate cereals, such as wheat (Triticum spp.) and barley (Hordeum vulgare), respond to prolonged cold by becoming more tolerant of freezing (cold acclimation) and by becoming competent to flower (vernalization). These responses occur concomitantly during winter, but vernalization continues to influence development during spring. Previous studies identified VERNALIZATION1 (VRN1) as a master regulator of the vernalization response in cereals. The extent to which other genes contribute to this process is uncle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
64
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(70 citation statements)
references
References 57 publications
6
64
0
Order By: Relevance
“…During cold treatments of 1 to 4 weeks, seedlings rarely emerged from the soil, but with longer cold treatments, the coleoptile typically emerged, as commonly observed in other cereals such as barley (Sasani et al, 2009;Greenup et al, 2010Greenup et al, , 2011. During the longest cold treatments, seedlings typically reached the first leaf stage, with the second leaf visible but not fully expanded.…”
Section: Natural Variation Of Vernalization and Photoperiod Requirementmentioning
confidence: 80%
“…During cold treatments of 1 to 4 weeks, seedlings rarely emerged from the soil, but with longer cold treatments, the coleoptile typically emerged, as commonly observed in other cereals such as barley (Sasani et al, 2009;Greenup et al, 2010Greenup et al, , 2011. During the longest cold treatments, seedlings typically reached the first leaf stage, with the second leaf visible but not fully expanded.…”
Section: Natural Variation Of Vernalization and Photoperiod Requirementmentioning
confidence: 80%
“…To test this prediction, we generated flowering data for representative taxa of cool-season Pooideae grasses and reconstructed vernalization responsiveness across the subfamily. Additionally, we leveraged genetic data on economically important crop species (Takahashi and Yasuda, 1971;Heide, 1994;Trevaskis et al, 2003;Yan et al, 2003;Preston and Kellogg, 2008;Greenup et al, 2011;Ream et al, 2014) to determine if orthologs of the vernalization gene VRN1, and the floral integrator VRN3, are cold responsive across the diversity of Pooideae. Our findings demonstrate that vernalization responsiveness is widespread in Pooideae and probably evolved early in the subfamily.…”
Section: Discussionmentioning
confidence: 99%
“…During this time, it is hypothesized that Pooideae became more cold tolerant (Sandve et al, 2008(Sandve et al, , 2011Sandve and Fjellheim, 2010;Preston and Sandve, 2013;Vigeland et al, 2013) and evolved a response to vernalization (Preston and Kellogg, 2008;Ream et al, 2012). Indeed, vernalization responsiveness has been identified in several so-called core group Pooideae (Davis and Soreng, 1993), such as wheat (Triticum aestivum), barley (Hordeum vulgare), oats (Avena sativa), and ryegrass (Lolium perenne), and a species sister to core Pooideae, Brachypodium distachyon (Brachypodieae; Takahashi and Yasuda, 1971;Heide, 1994;Trevaskis et al, 2003;Yan et al, 2003;Preston and Kellogg, 2008;Greenup et al, 2011;Ream et al, 2014). However, it is unknown whether vernalization responsiveness evolved at the base of the entire Pooideae, concomitant with the tropical to temperate zone transition.…”
mentioning
confidence: 99%
“…After short-term cold exposure, when the expression level of VRN1 is still very low, Oliver et al [120] found similar kinetics in the initial transcription of VRN1 and COR14B upon cold exposure (24 h) in barley. Under short photoperiods, high COR14B expression or positive correlation between expression of VRN1 and COR14B remained after long-term cold treatment in T. monococcum [112], barley [121], and meadow fescue [105]. COR14B is induced by CBFs, and barley VRN1 also has a putative CBF binding site in its promoter [122].…”
Section: Regulation Of Leaf Growth Versus Freezing Resistance In Springmentioning
confidence: 97%